Effect of school type and family income on motor competence changes in pre-school children: a repeated cross sectional study (Journal of Physical Education (Maringá), 2020)
Motor competence (MC) is an attribute associated with positive health behaviors; contextual factors, seems to play a important role for MC of children. The purpose of this study was to compare the MC of preschool children in two different years and to identify the effect of contextual factors (school type and family income). Two representative samples of children (3 to 5 years old) from Recife were assessed in two time periods: 2010 (n= 282 children, 151 boys) and 2012 (n=270 children, 148 boys). MC was assessed using the Test of Gross Motor Development - 2. Data analysis used the Anova Two-Way and the Ancova tests adjusted by type of school (public and private) and family income, a p